Peningkatan Kemampuan Analisis Krisis Mahasiswa melalui Metode Case Based Learning - Arianto Arianto; Romi Altavia; Disya Fatriana; Fitri Novyanti (-, 2026)
The dynamic development of organizational environments in the digital era requires students to possess critical thinking and crisis analysis skills to respond effectively to issues, crises, and reputation challenges. However, learning evaluation results indicated that students of the Communication Science Study Program at Universitas Selamat Sri still demonstrated relatively low capability in analyzing crisis cases. This study aimed to improve students’ crisis analysis and critical thinking skills through the implementation of the Case Based Learning (CBL) method. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model conducted in two cycles. Data were collected through crisis analysis tests, observations, documentation, interviews, and student reflections. The findings showed an improvement in students’ average scores from 68.4 in the pre-action stage to 85.3 in Cycle II, while learning mastery increased from 40.6% to 87.5%. In addition, students’ active participation during the learning process also increased. These findings indicate that Case Based Learning is effective in enhancing students’ crisis analysis abilities and critical thinking skills and is relevant for practice-oriented learning implementation in higher education.